PERAN END CHILD TRAFFICKING IN ASIAN TOURIM (ECPAT) DALAM MENANGGULANGINCHILD TRAFFICKING DI INDONESIA (2009-2012) - Yana, Aisyah Fitri; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The Roles of End Child Prostitution in Asian Tourims (ECPAT) in OvercomingÂ Child Trafficking in Indonesia. Â Child trafficking in Indonesia is still developing. SecondÂ position of Indonesia shown that there was lack of Â government efforts in overcoming childÂ trafficking. Some of the factors of child trafficking are; the lack of awareness of theÂ dangers of trafficking, poverty that caused immigration, sham occupations, lack ofÂ education, fake marriages and romances. And then governmentproved by working withÂ ECPAT in overcoming child trafficking in Indonesia. Â This study shown the efforts ofÂ ECPAT assist Indonesian government in overcoming child trafficking. Koalisi NasionalÂ Penghapusan Eksploitasi Seksual Komersial Anak (KONAS PESKA) is a assembly ofÂ activists who care about child trafficking issues. PreviouslyKONAS PESKA was an AffiliateÂ member of ECPAT International and thenit became ECPAT Indonesia. Advocacy is aÂ program that is often done by ECPAT Indonesia and some organizations of childÂ trafficking eradication for commercial sexual exploitation. Cooperation with The BodyÂ Shop in campaign âStop Sexual Children Trafficking and Youth Traffickingâ, an importantÂ advocacy component of the campaign is the Country Progress Card Â system is created byÂ ECPAT and The Body Shop will evaluate the progress of the countriesâ action in wiping outÂ of child trafficking in their countries.Key Word: Â Child Trafficking, Routine Activity theory, ECPAT Indonesia, Stop SexualÂ and Children trafficking and Youth Trafficking Campaign